2008
DOI: 10.3382/ps.2007-00519
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Maternal Corticosterone and Selection for Contrasting Adrenocortical Responsiveness in Japanese Quail on Developmental Instability of Female Progeny

Abstract: Differences in developmental instability were assessed in female offspring of Japanese quail hens selected for reduced (low stress, LS) or exaggerated (high stress, HS) plasma corticosterone (B) response to stress and treated with a placebo or B during egg formation. Hens of each line were implanted (s.c.) with either a silastic tube containing no B (controls) or one filled with B. Female chicks hatched from each of the 4 line x implant treatment combinations were retained for examination of 3 bilateral traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
0
15
2
Order By: Relevance
“…These results therefore indicate that at least in this rabbit model and for the compound applied, maternal stress does not result in elevated DI levels of offspring. This is an unexpected result because earlier studies that induced maternal stress through corticosterone or cortisol treatment in several bird and fish species, did find evidence for an increase in offspring DI [23][24][25]. In this study, the pregnant does responded to the treatment by feeding less and they gained less weight, which led to a reduction in pup weight and ossification.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…These results therefore indicate that at least in this rabbit model and for the compound applied, maternal stress does not result in elevated DI levels of offspring. This is an unexpected result because earlier studies that induced maternal stress through corticosterone or cortisol treatment in several bird and fish species, did find evidence for an increase in offspring DI [23][24][25]. In this study, the pregnant does responded to the treatment by feeding less and they gained less weight, which led to a reduction in pup weight and ossification.…”
Section: Discussioncontrasting
confidence: 42%
“…Secondly, previous studies on the effects of maternal glucocorticoids have used birds and fish as a model system [22][23][24][25], which are oviparous animals. In contrast, here we studied maternal stress in a mammal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were further corroborated by two studies that investigated two divergent genetic lines of Japanese quail selected for their high (HS) and low stress (LS) plasma corticosterone response to acute restraint stress. It was found that HS quail had significantly greater FA in the lengths of tibiotarsus and metatarsus bones, middle toe, and faces than LS quail [56,60].…”
Section: Postnatal Development Periodmentioning
confidence: 98%
“…The resulting experiments involved prenatal exposure to corticosterone and concomitant changes in body symmetry in birds. It was found that corticosterone treatment resulted in greater embryonic mortality, reduced growth, and increased FA in tarsus length in chickens and marginally elevated FA of the face length in Japanese quails [55,56]. A separate experiment manipulated cortisol concentrations in embryos of coral reef damselfish and explored the adverse effects on growth and survival.…”
Section: Prenatal Development Periodmentioning
confidence: 99%